"A woman's honor tumbles down on all of us in the family, but a man's honor is only his": young women's experiences of patriarchal chastity norms. Issue 1 (1st January 2021) - Christianson, Monica; Teiler, Åsa; Eriksson, Carola
ABSTRACT: Purpose : In this qualitative study we explored how young women living in Sweden with ethnic and cultural roots in the Middle East and East Africa comply with or resist so-called honour norms and how they perceive that these norms affect their living conditions. Method : In depth interviews were performed with 14 young women. The majority were between 21 and 32 years of age with a mean age of 24. All interviews were transcribed verbatim and a grounded theory approach was used. To reflect the diversity in women's experiences, the grounded theory approach was conducted from a feminist perspective to transform women's personal narratives to a larger social context. Results : We analysed the core category "Honorable women in becoming" as the central emerging phenomenon related to categories about structural and individual control of women, the women's adjustment and resistance, and the continuum of severe consequences and violence that they experienced in their struggle for autonomy. Conclusion : Simone de Beauvoir's feminist theory about women as "the other" was an inspiration and gave us valuable input to highlight women's experiences and situations from a perspective of gender, power, and oppression.